Copper molybdenum sulfide nanoparticles embedded on graphene sheets as advanced electrodes for wide temperature-tolerant supercapacitors. Issue 7 (29th May 2019) - Sahoo, Surjit; Krishnamoorthy, Karthikeyan; Pazhamalai, Parthiban; Mariappan, Vimal Kumar; Kim, Sang-Jae
Abstract : A novel copper molybdenum sulfide-graphene (Cu2 MoS4 -rGO) hybrid is investigated as an electrode for temperature tolerant supercapacitor. Abstract : A novel hybrid of Cu2 MoS4 nanoparticles embedded on reduced graphene oxide (rGO) sheets was prepared via a one-pot hydrothermal method without any surfactants or templates. The electrochemical properties of the as-prepared Cu2 MoS4 –rGO electrode were investigated as an advanced electrode for supercapacitor applications, and it exhibited higher specific capacitance (231.51 F g −1 at 5 mV s −1 ) compared to the pristine Cu2 MoS4 electrode (135.78 F g −1 at 5 mV s −1 ). The Cu2 MoS4 –rGO electrode showed energy density of 31.92 Wh kg −1 at a constant current of 1.5 mA, which was higher than that of the pristine Cu2 MoS4 electrode (17.91 Wh kg −1 at a constant current of 1.5 mA). The satisfactory enhancement in the electrochemical performance of Cu2 MoS4 –rGO electrodes could be attributed to the chemical interaction between rGO sheets and Cu2 MoS4 nanoparticles, which produced more active sites for the charging/discharging process and enabled fast electron transport through the graphene layers. Furthermore, this work presented an extensive study about the effect of temperature (from 25 °C to 80 °C) on the Cu2 MoS4 –rGO electrode in an aqueous Na2 SO4 electrolyte. The effect of temperature on the electrochemical properties of the Cu2 MoS4 –rGO electrode was investigated using cyclic voltammetry (CV), charge–discharge (CD) tests and electrochemical impedance spectroscopy (EIS). The electrochemical performance of the Cu2 MoS4 –rGO electrode exhibited ∼128% improvement at 80 °C compared to that at 25 °C in CD profiles. These experimental results indicate a fundamental comprehension of the temperature-dependent supercapacitor electrodes for industrial, military and space applications.